Plasma Engineering : Applications from Aerospace to Bio and Nanotechnology. - Keidar, Michael (Academic Press, 2013)
This book covers the field of plasma engineering, which applies the unique properties of plasmas (ionized gases) to improve processes and performance over many fields, such as materials processing, spacecraft propulsion, and nanofabrication. It addresses fundamentals of physics and modeling as well as new real-word applications in aerospace, nanotechnology, and bioengineering.